Pengaruh Ekstrak Labu Siam (Sechium edule (Jacq.) Swartz) Terhadap Waktu Koagulasi Pada Mus musculus - Nuralifah Nuralifah; Wa Ode Tika Ertia Wahid; Muhammad Ilyas Yusuf (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2015)
Chayote (Sechium edule (Jacq.) Swartz) is a type of vegetable that contains most of the calcium, the calcium in the blood which stimulates the release of thromboplastin phospholipid that will catalyze changes that have not been activated prothrombin into thrombin active. The purpose of this study was to prove the existance fromthe effect of squash extracts against coagulation time in mice. This study is experimental, which is divided into 5 treatment consisted of 3 repetitions. Extracts of squash as the test material is made a concentration of 100 mg / kg, 200 mg / kg, and 300 mg / kg. Observations made by looking fibrin threads formed on the fracture capillary tube ± for 2-6 minutes after exiting the first blood. The study was conducted in the laboratory of Pharmacology Bina Husada Kendari. Statistical analysis of the results obtained from the ANOVA showed that extracts of squash has an effective effect with 15.33 seconds at a concentration of 300 mg / kg. Results of ANOVA and LSD test showed extracts of squash has an effect on coagulation time significantly.Keywords: coagulation time, extract of squash, Sechium edule (Jacq.) Swartz